Silica catalyzed one pot synthesis of hybrid thiazolidin-4-one derivatives as anti-tubercular and anti-inflammatory agent by attenuating COX-2 pathway. Issue 20 (18th October 2019) - Pathak, Prateek; Shukla, Parjanya Kumar; Naumovich, Vladislav; Grishina, Maria; Potemkin, Vladimir; Verma, Amita
Abstract: A novel series of a hybrid class of hybrid thiazolidin-4-one derivatives were designed and synthesized through one-pot catalytic synthesis. The reaction was catalyzed in the presence of silica-H2 SO4 (+6) . The derivatives computational ADMET profile was calculated. The study shows that most active derivatives have optimal logP, higher anti-inflammatory activity score, and poor metabolism at the sight of P450-3A4 and 2D6. The entire series of derivatives were further evaluated for anti-tubercular (against Mycobacterium tuberculosis H37Rv (Resistant strain)) and anti-inflammatory activity (in-vivo assay using Wistar rat). The result showed that derivatives 4c, 4h, and 4m have significant potency against tested M. tuberculosis . However, derivatives 4i and 4j found significantly active against inflammation. In vitro COX inhibition assay also supported the result in favor of selectivity and efficacy of derivatives. GRAPHICAL ABSTRACT: